PENGARUH PEMBERIAN DOSIS PUPUK KASGOT (BEKAS MAGGOT) TERHADAP PERTUMBUHAN DAN HASIL TIGA VARIETAS JAGUNG MANIS (Zea mays Saccharata Sturt. L): Jagung Manis, Pupuk Kasgot, Pertumbuhan, Hasil - alberta, alberta; Santosa, Sartono Joko; Siswadi, Siswadi (Innofarm:Jurnal Inovasi Pertanian, 2024)
Research about the Effect of Dosage Kasgot Fertilizer (Maggot Ex) on the Growth and Yield of Three Varieties of Sweet Corn (Zea mays Saccharata Sturt. L) was carried out in Gempol Village, Karanganom, Klaten at an altitude of 225 meters above sea level, regosol soil type. The research aims to learn the best dose of kasgot organic fertilizer on the growth and yield of 3 varieties of sweet corn (Zea Mays Saccharata Sturt. L). This research used the RCBD (Randomized Completely Block Design) method which was arranged in separate plots (Split Plot) with 2 types of treatment factors. The types of treatment used are 3 varieties of sweet corn (bonanza, super sweet, and sweet boy) and kasgot organic fertilizer with 4 doses, K0 (0 gram/polybag), K1 (275 grams/polybag), K2 (375 grams/polybag), and K3 (475 grams/polybag). The data obtained were analyzed statistically using analysis of variance (ANOVA) and continued with the BNJ test at the 5% level. The research results show that: (1) The dosage of K3 kasgot organic fertilizer (475 grams/polybag) had a significant effect on the weight of the cobs is bloated, the weight of the cobs without husk, the diameter of cobs, and the number of rows of cobs so that it could increase the production of sweet corn plants. (2) The V2 variety (super sweet variety) provides the best growth while the V3 variety (sweet boy variety) provides the best production results. (3) The interaction of V2K1 treatment (super sweet variety and kasgot organic fertilizer 275 grams/polybag) provided the best growth in plant height with an average of 224.667 cm. The interaction of V2K3 (super sweet variety and kasgot organic fertilizer 475 grams/polybag) gave the best growth in the number of leaves with an average of 19,667cm. The interaction of V1K2 (bonanza variety and kasgot organic fertilizer 375 grams/polybag) provided the best diameter of stem growth with an average of 2,100 cm. The interaction of V3K3 treatment (sweet boy variety and kasgot organic fertilizer 475 grams/polybag) gave the best results on the weight of the cobs is bloated with an average value of 359,000 grams, the weight of cobs without husks with an average value of 264,333 grams, the diameter of cobs with an average value of 4,683 cm, and the number of rows of cobs with an average of 19,000 rows.